THE FORMATION OF MARKET STRATEGIES FOR THE POTATO BREEDING AND SEEDING COMPANIES - Chotkowski, Jacek; Rembeza, Jerzy (Acta Scientiarum Polonorum. Oeconomia, 2003)
This article presents the potato breeding and seeding companies, what illustrates the premises of the market strategy’s conception of seed industry in Poland. The strategy of those companies should include the following major elements:concentration of their potential, adequate seeding policy, development of distribution network, searching for new markets, also for constant ties with purchasers, introduction marketing orientation, activity on potato market, Outlined directions of business activity may prove useful in Polish seeding industry and also in other Middle-East European countries, which face problems of strengthening their market positions.